Determining the Seroprevalence of HIV Infection among Tuberculosis Patients in a Tertiary Care Hospital - Dipa M. Kinariwala (New Frontiers in Medicine and Medical Research Vol. 16, 2021)
Introduction: The Human Immunodeficiency Virus (HIV) is the most potent risk factor for Tuberculosis progression (TB). Surveillance of HIV among & TB patients has been recognized to be important as the HIV epidemic continues to fuel TB epidemic. In those who are infected with both HIV and TB, the interaction is bidirectional and synergistic. The purpose of this study was to determine the seroprevalence of HIV infection among patients with tuberculosis in a tertiary care hospital. Method: A one-year study of 4500 confirmed tuberculosis patients was conducted, and HIV antibodies were tested in accordance with National AIDS Control Organisation (NACO) guidelines. The results showed that 244 (5.42 percent) of the 4500 patients screened were HIV positive. The male to female ratio was 2.34 (171/73), and the prevalence of co-infection was highest among those aged 35 to 50 years. Conclusion: The current study found 5.42 percent HIV seroprevalence in tuberculosis patients. Early diagnosis of HIV infection in tuberculosis patients will allow for quicker access to care and treatment, including antiretroviral therapy (ART). This will reduce the number of deaths and illnesses among HIV-TB co-infected patients.